HOW ESG PERFORMANCE INFLUENCES FINANCIAL PERFORMANCE IN EUROPE: UNPACKING THE MEDIATION EFFECT OF GREEN INNOVATION - Widoretno, Esa Panganti; Choirunnisa, Anawinta; Nur Fajri, Mirza Aulia (UI Scholars Hub, 2025)
Background: Global sustainability challenges and EU regulations, such as Directive 2014/95/EU, drive firms to adopt ESG practices, yet their financial impact remains debated. ESG initiatives are increasingly important for transparency, competitiveness, and alignment with the UN Sustainable Development Goals. In this context, green innovation emerges as a potential pathway to transform ESG commitments into tangible business value. Method: This study employed a regression model using the SPSS PROCESS macro (Model 4) with bootstrapping (95% CI) to analyze direct and indirect effects of ESG, green innovation, and financial performance in European energy, utilities, materials, and industrial sectors. Findings: The results indicate that ESG does not significantly impact financial performance. While ESG dimensions positively influence green innovation, green innovation does not mediate the relationship between ESG performance and financial performance. Conclusion: Although ESG can stimulate green innovation, such innovation does not translate into improved financial outcomes. Companies should optimize their green innovation strategies and consider other influencing factors to ensure sustainability benefits contribute more effectively to financial performance. Novelty/Originality of this article: This study investigates green innovation as a mediating mechanism linking ESG performance to corporate outcomes across multiple European countries, advancing the literature beyond studies that assess only direct ESG effects.